Tangential interface stiffness estimation of dry-joint masonry structures through an extended experimental campaign - Colombo, Carla (2023)
Many monumental masonry structures, such as aqueducts and public or military constructions, have been built using regular units neatly dressed without mortar. Detailed numerical modeling is commonly utilized to simulate the behavior of such dry-joint structures, which necessitates the proper definition of various physical and mechanical input parameters to enhance the reliability of the results. Among them, the normal and tangential interface stiffness play a key role in simulating masonry (either mortared or dry-joint) structures. Despite their paramount importance, the existing literature lacks established experimental studies for their characterization, and importantly their comparative validation. To this end, this paper presented an extensive experimental campaign on limestone blocks focusing on the estimation of the tangential interface stiffness. Two intrinsically different methodologies were employed for the tangential interface stiffness description, aiming to obtain reliable and cross-validated results. The first methodology, namely deformation-based, used direct shear-box tests and measured the interface shear deformation upon shear stresses for different levels of normal stress. The second methodology, namely vibration-based, utilized ambient vibration noise to measure the natural frequencies of the dry-stack assembly, which was correlated with the tangential interface stiffness through an inverse dynamic analysis. The dependence of the tangential interface stiffness with respect to the normal stress acting at the interface was discussed and the two methodologies were compared and validated.